Translation as interpretation: a hermeneutical inquiry into the semantics of the Scriptural Language - Solihu, Abdul Kabir Hussain (2011)
Translation makes mutual understanding possible across diverse cultures and localities. There are different theories of translation each aspiring to objectively represent the original meaning or focus on important aspects of the original text. Our understanding and expression of, in particular, abstract meaning is largely seen in terms of historically and culturally shaped language, and long before we control any linguistic discourse, our undersigning is said to have been shaped by it.